Giberelic acid does not promote positive effect on seedlings of ’Okinawa’ peach rootstock - Gonçalves, Bruno Henrique Leite; Souza, Jackson Mirellys Azevedo; Leonel, Sarita; Silva, Marcelo de Souza; Bolfarini, Ana Carolina Batista; Modesto, Joyce Helena (Acta Iguazu, 2018)
The quality of seedlings is essential for a successful crop cycle, since they are the basis of the orchard; and directly linked to its future performance. In peaches, obtaining rootstock is one step process for the production of the plants, which can be often increased by using plant growth regulators. In this way, this study aimed to evaluate the response of gibberellic acid to grow ‘Okinawa’ peach seedlings rootstock. The experimental design was a randomized complete block, consisting of four treatments (0, 25, 50 and 75 mg L-1 GA3); three subplots (30, 60 and 90 days after transplanting the seedlings) in 10 repetitions with 30 plants per treatment. All the experiment was conducted in the nursery with shade cloth (70%). Evaluations consisted of plant height (cm); root length (cm); stem diameter (mm); leaf area; specific area and leaf number; leaf matter; fresh and dry stem matter (g); fresh and dry root matter (g). Thereby, doses of gibberellic acid did not present any statistical significance on the growth of ‘Okinawa’ peach seedlings rootstock; thus it should be considered future evaluation of this phytoregulator at higher doses.